Edge flourish and phase transfer cell culture in agarose scaffold for articular cartilage tissue engineering. - Cheng, He. (2009)
Agarose hydrogel is a widely used scaffold for cartilage tissue engineering. In this project, we aim to look into a commonly seen phenomenon of edge flourish in prolonged in vitro culture of chondrocytes in agarose. The histological and morphological properties of edge flourish were characterized, and the biochemical mechanisms behind this phenomenon, such as gene transcriptional activities were investigated to provide an explanation for the superiority in histology and ECM secretion of edge flourish. Then we tried to establish a protocol to introduce this phenomenon into the agarose hydrogel bulk. Cavity was created inside agarose hydrogel bulk for creating free space to simulate the environment of hydrogel surface, and cells demonstrated phase transfer cell growth (PTCG) in the cavity. Experiments also showed neotissue formed in the cavity resembled the characteristics of edge flourish. Novel scaffold was constructed to exploit the merits of PTCG. It can be suggested from these results that this novel scaffold has great potential to be used in regeneration of cartilage tissue.